Hypomagnesaemia in cases of alcohol use disorder: a cross-sectional study - Motlag, Mrinalini D.; Patel, Azharuddin Rafique (International Journal of Research in Medical Sciences, 2025)
Background: Alcohol withdrawal syndrome is a frequent and life-threatening condition experienced in alcohol use disorder (AUD). Hypomagnesaemia has been commonly reported in cases of AUD. This study aims to estimate serum magnesium level in cases of AUD and to study its association with clinical presentations in tertiary care institute. Methods: This is a cross-sectional study that involved 120 patients of AUD with various presentations and diagnosis of AUD was made using diagnostic and statistical manual of mental disorder, fifth edition (DSM-5) criteria. Severity of alcohol withdrawal was assessed with revised clinical institute withdrawal assessment for alcohol scale (CIWA-Ar). Serum magnesium was estimated using colorimetric end point method. Normal range of serum magnesium 1.46 to 2.68 mg/dl was taken. Results: In this study the mean age of the subjects with AUD was 38.9±10.8 years and range 18 to 66 years. Males constitute 96.67% and females constitute 3.33%. Out of 120 cases we have observed 63.33% (76 cases) had normal magnesium level, while 36.67% (44 cases) had hypomagnesaemia. Serum magnesium in cases of AUD with withdrawal was significantly lower as compared to cases of AUD without withdrawal. The lowest level of serum magnesium was seen in patients with alcohol withdrawal with seizures. Conclusions: Hypomagnesaemia was noted in about one-third cases of chronic AUD and serum magnesium was significantly decreased in cases presenting with alcohol withdrawal.